Glaciological history and structural evolution of the Shackleton Ice Shelf system, East Antarctica, over the past 60 years - Thompson, Sarah S.; Kulessa, Bernd; Luckman, Adrian; Halpin, Jacqueline A.; Greenbaum, Jamin S.; Pelle, Tyler; Habbal, Feras; Guo, Jingxue; Jong, Lenneke M.; Roberts, Jason L.; Sun, Bo; Blankenship, Donald D. (The Cryosphere, 2023)
The discovery of Antarctica's deepest subglacial trough beneath the Denman Glacier, combined with high rates of basal melt at the grounding line, has caused significant concern over its vulnerability to retreat. Recent attention has therefore been focusing on understanding the controls driving Denman Glacier's dynamic evolution. Here we consider the Shackleton system, comprised of the Shackleton Ice Shelf, Denman Glacier, and the adjacent Scott, Northcliff, Roscoe and Apfel glaciers, about which almost nothing is known. We widen the context of previously observed dynamic changes in the Denman Glacier to the wider region of the Shackleton system, with a multi-decadal time frame and an improved biannual temporal frequency of observations in the last 7 years (2015–2022). We integrate new satellite observations of ice structure and airborne radar data with changes in ice front position and ice flow velocities to investigate changes in the system. Over the 60-year period of observation we find significant rift propagation on the Shackleton Ice Shelf and Scott Glacier and notable structural changes in the floating shear margins between the ice shelf and the outlet glaciers, as well as features indicative of ice with elevated salt concentration and brine infiltration in regions of the system. Over the period 2017–2022 we observe a significant increase in ice flow speed (up to 50 %) on the floating part of Scott Glacier, coincident with small-scale calving and rift propagation close to the ice front. We do not observe any seasonal variation or significant change in ice flow speed across the rest of the Shackleton system. Given the potential vulnerability of the system to accelerating retreat into the overdeepened, potentially sediment-filled bedrock trough, an improved understanding of the glaciological, oceanographic and geological conditions in the Shackleton system are required to improve the certainty of numerical model predictions, and we identify a number of priorities for future research. With access to these ...